Predictors of delayed hyponatremia after endoscopic transsphenoidal surgery for non-functioning pituitary adenomas - Lu, Xiaocheng; Sun, Jingshan; Wang, Yifan; Huang, Yunfan; Wang, Zhong; Chen, Gang (Frontiers in Endocrinology, 2025)
BackgroundDelayed postoperative hyponatremia (DPH) is a unique complication of endoscopic transsphenoidal surgery (TSS). Predictive factors for DPH following TSS in patients with nonfunctioning pituitary adenoma (NFPA) has not been well established. The aim of this study was to evaluate possible predictive factors related to DPH in patients with NFPA after TSS.MethodsWe retrospectively analyzed 377 consecutive patients who underwent TSS for a NFPA between 2020 and 2024. The patients’ demographics, clinical features, as well as preoperative, intraoperative and postoperative data were collected, with statistical analysis of each factor performed.ResultsAmong the 377 patients with NFPA, DPH occurred in 112 (29.7%), including 24 (21.4%) had moderate hyponatremia and 13 (11.6%) had severe hyponatremia. Patients in DPH group had higher preoperative TSH level (3.01 vs 2.37 mIU/L, p=0.038), higher rates of intraoperative CSF leak (28.6% vs 16.6%, p=0.009) and postoperative meningitis (17.9% vs 7.5%, P = 0.004). In addition, hypertension (OR = 0.55, 95%CI 0.35-0.89, p=0.014), higher serum sodium of postoperative day 1 (POD 1) (OR = 0.88, 95%CI 0.83-0.94, p<0.001), and arginine vasopressin deficiency (AVP-D) (OR = 0.40, 95%CI 0.17-0.92, p=0.031) were linked to lower rates of DPH. In the multivariate analysis, hypertension (OR = 0.51, 95%CI 0.31-0.86, p=0.011), intraoperative CSF leak(OR = 2.60, 95%CI 1.40-4.81, p=0.002), serum sodium of POD 1(OR = 0.90, 95%CI 0.84-0.97, p=0.003), preoperative TSH(OR = 1.13, 95%CI 1.01-1.26, p=0.031) and meningitis(OR = 3.75, 95%CI 1.38-10.18, p=0.010) were identified as independent risk factors for DPH after TSS.ConclusionThis study identified the independent risk factors for delayed hyponatremia in patients with NFPA after TSS, including higher preoperative TSH level, intraoperative CSF leak, lower serum sodium of POD 1 and meningitis. However, patients with hypertension had a higher likelihood of avoiding DPH. It is recommended that DPH should be closely monitored after endoscopic TSS, especially in patients without hypertension. Furthermore, a multicenter prospective trial with an expanded sample size is warranted to investigate the etiology of DPH after endoscopic TSS.